PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL GRAND ZURI PEKANBARU - Ardiyanti, Ayu Mila; Sutrisna, Endang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to determine the effect of customer relationship management and service quality on customer loyalty at Hotel Grand Zuri Pekanbaru partially and simultaneously. Customer relationship management and service quality as the independent variable (X1 & X2) mean while customer loyalty as the dependent variable (Y). This research was conducted at Hotel Grand Zuri Pekanbaru which is located at Jalan Teuku Umar No. 7 Rintis Pekanbaru. In this research the data analysis methodology used is descriptive and quantitative with SPSS version 23.0 program, where the sample in this research is customer of Hotel Grand Zuri Pekanbaru as many as 100 respondents. To determine the sample using slovin formula, sampling technique non-probability sampling with purposive sampling technique. Data collection technique through observation, interview and questionnaire, type and source data of using primary and secondary, measurement technique using a likert scale.From the research test covering validity test, reliability test, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial) and F (simultaneous) test. The result of this research shows that the result of test first t test hypothesis, customer relationship management to customer loyalty is t arithmetic (12,707) > t table (1,6605) meaning that customer relationship management have significant effect to customer loyalty. Second, service quality to customer loyalty is t arithmetic (11,809) > t table (1,6605) meaning service quality have a significant effect on customer loyalty. F customer relationship management test and service quality to customer loyalty are F arithmetic (108,006) > F table (3,09). This means customer relationship management and service quality simultaneously significantly influence customer loyalty.